Paranaitis abyssalis - Kato, Tetsuya; Pleijel, Fredrik (Zenodo, 2003)
PARANAITIS ABYSSALIS (HARTMANN- SCHRÖDER, 1975) (FIG. 4) Pareteone abyssalis Hartmann-Schröder, 1975: 57–59, figs 19–21. Paranaitis abyssalis : Pleijel, 1991: 258. Distribution Treurenberg Bay, Spitsbergen, Atlantic coast of Norway, Greenland (Wesenberg-Lund, 1953), Goose Fjord, Canada (Ditlevsen, 1909), Kara Sea (Fauvel, 1911), Iceland (Wesenberg-Lund, 1951), Sweden (Pleijel & Dales, 1991), Gibraltar Strait (Pleijel, 1993a), Chukchi Sea. Material examined Holotype (HZM-P-13605), off Iberian Peninsula, 42∞55.4¢N, 14∞07.9¢W, 5260 m. Description Holotype lacking posterior end, 15 mm long, 1.3 mm wide, for 52 segments. Body colour of live animals unknown; preserved specimen uniformly pale. Body cylindrical. Prostomium anteriorly rounded, with distinct deep ligula (Fig. 4A). Paired antennae and palps of holotype all lost or damaged. Eyes absent. Nuchal papilla with rounded end, slightly longer than wide, inserted posteriorly in ligula. Paired large, rounded Published as part of Kato, Tetsuya & Pleijel, Fredrik, 2003, A revision of Paranaitis Southern, 1914 (Polychaeta: Phyllodocidae), pp. 379-429 in Zoological Journal of the Linnean Society 138 (4) on page 388, DOI:10.1046/j.1096-3642.2003.00069.x, http://zenodo.org/record/5437920